Genome-wide DNA methylation analysis of human peripheral blood reveals susceptibility loci of diabetes-related hearing loss. Issue 12 (December 2018) - Hao, Jin; Hua, Lin; Fu, Xinxing; Zhang, Xuelian; Zou, Qijuan; Li, Yongxin
Abstract Diabetes-related hearing loss (DRHL) is a complication of diabetes mellitus that is drawing more attention currently. DNA methylation has a critical role in the pathogenesis of type 2 diabetes mellitus (T2DM) and its complications. Therefore, we investigated the genome-wide DNA methylation of peripheral blood of T2DM patients with/without hearing loss in order to explore the susceptibility loci of DRHL. Between DRHL group and control group, 113 gene sites were identified to be differentially methylated regions (DMRs). Among 38 DMRs with whole samples, the classification accuracy is up to 90%. With alignment to T2DM susceptibility genes and deafness genes published, KCNJ11 was found to be the only overlapped gene. The DNA methylation level of KCNJ11 was associated with stroke (t  = 2.595, p  < 0.05), but not with diabetic nephropathy and diabetic retinopathy. The detective rate of distortion product otoacoustic emissions (DPOAE) from low to high frequencies (0.7–6 kHz) on the right ear was significantly correlated with the methylation level of KCNJ11. The auditory brainstem response (ABR) threshold on the right ear was also correlated (r  = 0.678, p  < 0.05). This DNA methylation profile indicates the susceptibility loci of DRHL. The potassium metabolism may have a critical role in the hearing loss caused by hyperglycemia.